The Implication Of Computerized System-Based Mortgage Right Registration - I Putu Arwan Puspa Resmawan; Any Andjarwati (Warmadewa Press, 2018)
The Circular No. 5/SE-100/I/2015 dated January, 29th 2015 issued by the Ministry of Agrarian and Spatial Planning/Head of National Land Agency, gives order to all ranks of working environment of the Land Agency to use the computerized system in the service of land registration, as long as the facilities and infrastructures are adequate. The strategy is aimed at; easing the access to land registration services for society and modernizing the agrarian management and service, Spatial Planning, and Land service. This is due to some reasons, which also affects the Mortgage Right registration system which, according to respondents, more than one registration of deed of imposition of mortgage but still in one credit agreement, cannot be registered at the same time. This study is an empirical research or non-doctrinal legal research. With regard to this the present study examines implementation of Mortgage Right registration at the Land Office of Badung District based on a computerized system after the issuance of the Circular 5/2015, to identify the obstacles faced in registering Mortgage Right in that new system and to seek for solutions to solve it.